PENGARUH PERAN GANDA, STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PEREMPUAN DI PT PHAPROS TBK KOTA SEMARANG - Rina Indra Iswari; Ari Pradhanawati (Universitas Diponegoro, 2017)
The work force in indonesia along the development of the changes. One of the amendments that is an influx of women in the work force. PT Phapros Tbk is one of the companies in semarang have female employees who in 2013 until 2016 an up and down in attendance or absentee fluctuant. Both are permitted employee performance can be seen from the dual role, job stress and motivation work.The purpose of this research is to find influence the dual role, job stress and motivation work on performance female employees in pt phapros tbk semarang city. Type research is explanatory research, to technique data collection through the questionnaire and interview. The sample techniques used technique purposive sampling. Sample 100 respondents were is an employee women pt phapros tbk semarang. This research using a technique the quantitative analysis. The quantitative analysis use the validity, reliability test, a correlation coefficient, regression analysis simple and multiple, the coefficients determination, the significance ( test T and test F ).This research result indicates that there was a correlation in the category of strong between variables the dual role, job stress, and motivation work of the performance of employees where the value of r of 0,579. Variable free third was proven have a positive influence and significantly to employee performance. Evidenced by the results of the test positive regression of 0,146 to the dual role, 0,025 for stress work and motivation 0,307 to work. The f count of 16,168 greater than f table (2,703).Based on the results of the study, the researchers suggest PT Phapros tbk. to be able to create a pleasant working environment, manage stress well, pay attention to the quality and quantity of results of work of employees.